PERAN MEKANISME CORPORATE GOVERNANCE DAN INDIKATOR EKONOMI MAKRO TERHADAP FINANCIAL DISTRESS - Masripah, Masripah; Beno, Benita Salsabila (Berkala Akuntansi dan Keuangan Indonesia, 2024)
This study aims to analyze the role of corporate governance mechanisms consisting of audit committee and managerial ownership and also macroeconomic indicators consisting of inflation and interest rates on financial distribution in infrastructure, transport and logistics companies listed on the Indonesian Stock Exchange for the period 2019-2021. This study used a quantitative approach with secondary data sources in the form of financial statements and corporate annual reports. The samples used in this study were 68 companies with a total of 204 firm year with purposive sampling methods. Data analysis techniques used include regression model selection tests, classical assumption tests, multiple regression analysis tests, and hypothesis tests with the STATA 16 program. The results showed that managerial ownership had a significant and negative impact on financial distress, and interest rate had a significant and positive impact on financial distress. Meanwhile, the other variables include: audit committee and inflation do not have significant impact on financial distress. This study will provide information that can assist to anticipating financial distress by improving the corporate governance mechanisms and understanding of macroeconomics studies.